Peran Gabungan Kelompok Tani (Gapoktan) Dalam Pemberdayaan Petani Kebun Sayur Desa Beruge Darat Kecamatan Talang Ubi Kabupaten Pali - Nawati, Iis; Suryati , Suryati; Muzaiyanah, Muzaiyanah (CV. ITTC INDONESIA, 2023)
This study discusses the role of combined farmer groups (GAPOKTAN) in empowering vegetable garden farmers in Beruge Darat Village, Talang Ubi District, Penukal Abab Lematang Ilir (PALI) Regency, which is an activity carried out by the government and Gapoktan for the benefit of the farming community. This is because most of the villagers work as farmers and their empowerment is very dependent on the human resources in it. If human resources have high motivation, and are able to raise awareness of their potential, the lives of farmers in the village will definitely improve. This research is motivated by problems related to difficulties in obtaining capital, knowledge and skills are still low, agricultural productivity is low which can affect the ability of farmers to carry out, for example, the quality of production inputs is not good, difficulties in supplying water for farming because farming land has a long distance far from a water source. The purpose of this study was to find out first what is the role of Gapoktan in empowering vegetable garden farmers in Beruge Darat Village, Talang Ubi District, PALI Regency, secondly, what are the obstacles faced by Gapoktan in empowering vegetable garden farmers in Beruge Darat Village, Talang Ubi District, Regency PALI in community empowerment in the agricultural sector. This type of research uses qualitative techniques, this type of field research, the subject of this research is the chairman of the Gapoktan, and there are four members. Data collection techniques carried out by researchers are observation, interviews, and documentation through data analysis techniques: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that Gapoktan plays a role in fulfilling its mission of empowering the community as a central institution, being involved in channeling government assistance, namely providing agricultural production facilities such as fertilizers, poisons, public wells and seeds, indicating that they play a role in carrying out extension activities and skills training for farmers.